Der neue Pauly - Supplemente - Landfester, Manfred; Schneider, Helmuth; Cancik, Hubert; Rüpke, Jörg (Der neue Pauly, 2004)
Ergänzen den NEUEN PAULY um vertiefende Daten und Fakten
Bis Bd. 7 Hrsg.: Hubert Cancik
Später: Herausgeber: Manfred Landfester, Jörg Rüpke, Helmuth Schneider
Keywords: Wörterbuch; Geschichte; Römisches Reich; Griechenland; Antike